Aswaja Material Learning Assistance with Peer Learning Method - Ghifari, Muhammad; Masdar, Moh (Communautaire: Journal of Community Service, 2024)
This study discusses the assistance of learning Aswaja material through the application of peer learning methods in the religious education environment at the madrasah tsnawiyah level. The peer learning method was chosen as an approach to increase students' understanding and involvement in learning Aswaja concepts. This mentoring process involves students as facilitators in study groups, where they share knowledge and learning experiences with each other. A qualitative approach was used in this study, with case studies as the main framework. The research participants consisted of students, teachers, and school administrators who were directly involved in the learning process. Data was collected through interviews, participatory observations, as well as analysis of curriculum documents and evaluation of student learning outcomes. The results of the study show that the use of the peer learning method in Aswaja learning is able to increase student engagement, strengthen understanding of the material, and encourage collaboration between students. Challenges faced in the application of this method include differences in abilities between students and the need for facilitator training to be more effective in guiding groups. The discussion highlights the implications of these findings for the development of the Aswaja learning method in religious education institutions as well as strategic recommendations to optimize the application of peer learning methods to improve the quality of education.